Evaluation of the Baitul Arqam Program at the Muhammadiyah Regional Leadership School - Nurul Hikmah Kartini; Verawati Verawati; Gufron Amirullah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The transformation of Muhammadiyah Organization values must be guaranteed to every citizen, whether at the level of leadership, cadres, members and even sympathizers. The form of cadre in the form of Baitul Arqam must be held at all levels in each region. This study generally aims to determine the effectiveness of the implementation of the Baitul Arqam program evaluation for teachers and employees in elementary and middle schools in the Muhammadiyah area of Palangka Raya City. The approach used in this research is the CIPP evaluation model. The research subjects came from all elements involved in the Baitul Arqam program for Elementary and Middle School Employees in Central Kalimantan, namely: 1) Principal; 2) Teacher; and 3) Education Personnel. The techniques used in this research are interviews. Checking the validity of the data was also carried out by confirming the data to the Muhammadiyah Central Kalimantan Regional Leadership for Primary and Secondary Education. The results of this study are as follows: (1) Analysis of the needs and goals and objectives of the program in the context component in the excellent category. (2) The strategy on the input aspect is included in a good category. (3) the implementation of activities in the process aspect is in a good category. (4) The product of the program is in a good category. The conclusion of this evaluation is the Baitul Arqam program for teachers and employees in elementary and middle schools in the Muhammadiyah area of Palangka Raya City will continue with several improvements.